(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
The paper aims to investigate objects located in railway natural industrial complexes, e.g. the Kuybyshevskaya Railway within the boundaries of Samara region. The authors analyse its following characteristic properties: geometric (proximity to water bodies); intercepted (crossings with bridges or waterbodies); watercut (proximity to subsurface water outlets and high groundwater); hilly-mountainous terrain (washouts and washaways); violation of surface (water drainage from the walls, washaways of flood-prone slopes). The researchers studied a schematic map of the Kuybyshevskaya Railway and came to the conclusion that there is a considerable number of railways crossings with water objects in Samara region, Ulyanovsk region and the Republic of Tatarstan. Some of these railways crossings are located in close proximity to waterbodies. The average value of the crossings is 0.549 km for every 1 km, i.e. approximately every 500 m railway tracks cross at least one water object. It means that there is a surface run-off coming from railroad tracks and near-by territories into a waterbody every 500 m. Systematic monitoring of water pollution is performed by a considerable number (up to 20) of gauging stations located within all railroad tracks in Samara region.